how to solve (8-5 ÷ 6) 6 = 43?

8 Answers

Relevance
  • 1 month ago
    Favorite Answer

    (8 - 5 ÷ 6) 6

    as written, we divide first:

    (8 - 5/6) 6

    Now we subtract, so we'll need a common denominator:

    (48/6 - 5/6) 6

    (43/6) 6

    Now multiply.  the 6's cancel out:

    43

  • Apply PEMDAS

    (8-5/6)6

    ((8*6-5)/6)6

    ((48-5)/6)6

    (43/6)6

    =43

  • 1 month ago

    What operand symbol is in the place of my underline ... ")_6" AND THE ANSWER IS * (as in the times sign) ... and then the equation works.

  • sepia
    Lv 7
    1 month ago

    (8 - 5 ÷ 6) 6 

    = 43

  • How do you think about the answers? You can sign in to vote the answer.
  • 1 month ago

    nothing to solve

    (8-5 ÷ 6) 6 

    division has precedence 

    (8 – 5/6)5

    (48/6 – 5/6)6

    (43/6)6

    43

    so the equality is correct.

  • 1 month ago

    By distributive law:

    (a - b) × c = a × c - b × c

    Now,  a = 8,  b = 5 ÷ 6  and  c = 6

    Hence, (8 - 5 ÷ 6) × 6

    = 8 × 6 - 5 ÷ 6 × 6

    = 48 - 5

    = 43

  • 1 month ago

    (8 - 5 ÷ 6) 6 

    = 43

  • 1 month ago

    you need to restate your question...looks like you have a typo

Still have questions? Get your answers by asking now.